Editorial - Anna-Lena Kempe (Stockholm University Press, 2013)
In this issue we will elaborate further on the discussion about different conceptions of 'design'. Design stems from the Latin word 'designo' which meant depicting. In Swedish and in English 'design' was historically used about maps or sketches of ships and buildings. Design then was more or less thought of as a practical device for creating an object that already existed in our minds or as intentions of God. The possibility to represent salient features of an object before it was built had many advantages in relation to constructions made in a process of trial-and-error.